CTLs are targeted to kill β cells in patients with type 1 diabetes through recognition of a glucose-regulated preproinsulin epitope - Skowera, Ania (American Society for Clinical Investigation, 2008)
The final pathway of β cell destruction leading to insulin deficiency, hyperglycemia, and clinical type 1 diabetes is unknown. Here we show that circulating CTLs can kill β cells via recognition of a glucose-regulated epitope. First, we identified 2 naturally processed epitopes from the human preproinsulin signal peptide by elution from HLA-A2 (specifically, the protein encoded by the A*0201 allele) molecules. Processing of these was unconventional, requiring neither the proteasome nor transporter associated with processing (TAP). However, both epitopes were major targets for circulating effector CD8(+) T cells from HLA-A2(+) patients with type 1 diabetes. Moreover, cloned preproinsulin signal peptide–specific CD8(+) T cells killed human β cells in vitro. Critically, at high glucose concentration, β cell presentation of preproinsulin signal epitope increased, as did CTL killing. This study provides direct evidence that autoreactive CTLs are present in the circulation of patients with type 1 diabetes and that they can kill human β cells. These results also identify a mechanism of self-antigen presentation that is under pathophysiological regulation and could expose insulin-producing β cells to increasing cytotoxicity at the later stages of the development of clinical diabetes. Our findings suggest that autoreactive CTLs are important targets for immune-based interventions in type 1 diabetes and argue for early, aggressive insulin therapy to preserve remaining β cells.